2004
DOI: 10.1111/j.1442-2050.2004.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Impedance characteristics of esophageal motor function in achalasia

Abstract: Detailed data on patterns of esophageal bolus transport in patients with achalasia are still lacking. To study these we applied the novel technique of multichannel intraluminal impedance measurements. Ten patients with achalasia were studied using a 16 channel system. Liquid and semisolid boluses of 10 mL were applied with the patients in a supine position. Patterns of bolus transport were determined and analyzed as compared to results obtained from 20 healthy subjects. The healthy subjects featured a unique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
3
28
1
1
Order By: Relevance
“…5 Impedance manometry tracing of a patient with pronounced chalasia in its late stages. The propulsion of the food bolus occurs in a delayed and variable manner, partly with evidence of regurgitation [20]. In the entire esophagus, coordinated propulsive transport is absent.…”
Section: Therapy Of Chalasiamentioning
confidence: 99%
See 1 more Smart Citation
“…5 Impedance manometry tracing of a patient with pronounced chalasia in its late stages. The propulsion of the food bolus occurs in a delayed and variable manner, partly with evidence of regurgitation [20]. In the entire esophagus, coordinated propulsive transport is absent.…”
Section: Therapy Of Chalasiamentioning
confidence: 99%
“…The food bolus fails to be transported by coordinated propulsion since the esophageal motility is diminished. The stretch sphincter segment does not open properly (frequency around 4% of patients with GERD [11, 13, 16]) manometry measurements obtained from patients suffering from this disorder [20].…”
Section: Impedance Manometry In Patients With Chalasia ("Achalasia")mentioning
confidence: 99%
“…Normal values for combined impedance monitoring and manometry (solid-state catheter) have been reported by three groups. 13,16,17 Tutuian et al 13 proposed normal values for impedance parameters for liquid and viscous swallows based on a multicentre study including 43 healthy American subjects. More than 93% of individuals with manometrically normal studies were found to have at least 80% swallows with complete liquid or at least 70% swallows with complete viscous bolus transit.…”
Section: Methodology and Normal Valuesmentioning
confidence: 99%
“…Similar bolus transit parameters were described in a study including 25 healthy German subjects. 16 Normal values of baseline impedance values and deglutitive impedance gradient during saline and semisolid (yogurt) bolus transit were also provided. On the basis of a study in 18 HV, Chen and Yi 17 reported that Chinese subjects with 70% or more complete bolus transit for either liquid or viscous are considered as having normal transit.…”
Section: Methodology and Normal Valuesmentioning
confidence: 99%
See 1 more Smart Citation